HEDGES, BOOSTERS, AND TAG QUESTIONS USED BY BANJARESE MEN AND WOMEN - Ninuk (TEFLA Journal (Teaching English as Foreign Language and Applied Linguistics Journal), 2019)
The main focus of this study is to investigate how Banjarese men and women use hedges, boosters, and tag questions in their conversations. By analyzing how language features used by different genders in Banjarmasin, it is hoped that gender-based social segmentation in the given society can be revealed. The data of this study are taken from three conversations with all-men participants, all-women participants, and cross-gender participants. The conversations investigated are transcribed before analyzed using interactional sociolinguistics approach. From this study, it is found that Banjarese women use more hedges than its men. Moreover, the frequency of boosters and tag questions used by both genders is not significantly different. However, Banjarese men commonly use tag questions for politeness purpose, while women mostly use them for showing uncertainty. As the conclusion, based on their frequencies and purposes of using hedges, boosters, and tag questions, women and men’s position in Banjarese society are still unequal. Banjarese women tend to be more aware of their roles in the society that it affects their language choices.